REFRACTORY OF WELL-DIFFERENTIATED THYROID CANCER TO THE TREATMENT WITH RADIOACTIVE IODINE - P. O. Rumyantsev (Opuholi Golovy i Šei, 2015)
Resistance of well-differentiated distant metastases to radioactive iodine treatment severely deteriorate survival prognosis of patients. Chemotherapy (doxorubicin and combinations) and retinoid acid analoques (isotretinоin, roaccutan) implimentation did not allow to recommend them as a therapy of choice. Effectiveness of several multikinase inhibitors (vandetanib, sorafenib, sunitinib) was confirmed in phase II clinical trials. In result of phase III clinical trial of sorafenib (reported on ASCO’2013, Chicago, USA) its therapeutic efficacy in patient with iodine-refractory well-differentiated thyroid cancer was affirmed.